2022
DOI: 10.14421/jiska.2022.7.1.10-19
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Sentimen Tweet Tentang UU Cipta Kerja Menggunakan Algoritma SVM Berbasis PSO

Abstract: Support Vector Machine (SVM) is one of the most widely used classification algorithms for sentiment analysis and has been shown to provide satisfactory performance. However, despite its advantages, the SVM algorithm still has weaknesses in selecting the right SVM parameters to optimize the performance. In this study, sentiment analysis was done with the use of data called tweets about Undang-Undang Cipta Kerja which reap many pros and cons by the people in Indonesia, especially the laborers. The classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…This algorithm combines distinct features in a way that minimizes losses, reducing the number of features while retaining the most informative ones. When it comes to using Indonesian text, SVM was compared to LR, and it produced superior results compared to LR [19]. When the two algorithms are compared, it is evident that SVM is deterministic and logistic regression is probabilistic.…”
Section: Discussion and Comparative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This algorithm combines distinct features in a way that minimizes losses, reducing the number of features while retaining the most informative ones. When it comes to using Indonesian text, SVM was compared to LR, and it produced superior results compared to LR [19]. When the two algorithms are compared, it is evident that SVM is deterministic and logistic regression is probabilistic.…”
Section: Discussion and Comparative Analysismentioning
confidence: 99%
“…The data points closest to the hyperplane are commonly referred to as support vectors. Previous research has indicated that when combined with Particle Swarm Optimization (PSO), SVM can achieve an accuracy rate of 95% in the sentiment analysis process [19].…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%